2007
DOI: 10.1080/00480169.2007.36764
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to macrocyclic lactone anthelmintics and associated risk factors on sheep farms in the lower North Island of New Zealand

Abstract: Anthelmintic resistance, and particularly ML resistance, was widespread on sheep farms in the Taihape area, and mostly involved O. circumcincta. The prevalence of resistance was lower on farms on which management practices, particularly those involving lambs, maintained refugia of unselected nematodes. Further investigation is required to develop control strategies which minimise selection for resistant worms, and how these may vary with climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…In New Zealand, an analysis of sheep AR through a field survey indicated refugia as an important risk factor (HUGHES et al 2007). Their results showed that the prevalence of AR was higher on farms on which more than 50% of lambs were weaned onto paddocks not grazed for a long period by lambing ewes and where lambs were not always returned to the same paddock after drenching.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, an analysis of sheep AR through a field survey indicated refugia as an important risk factor (HUGHES et al 2007). Their results showed that the prevalence of AR was higher on farms on which more than 50% of lambs were weaned onto paddocks not grazed for a long period by lambing ewes and where lambs were not always returned to the same paddock after drenching.…”
Section: Discussionmentioning
confidence: 99%
“…Early recommendations for sustainable parasite control were either based on evidence regarding key molecular processes involved in selection for resistance (Dobson et al, 2001), or simulation models (Leathwick et al, 1995). In recent years, several observational studies (Suter et al, 2004;Lawrence et al, 2006;Hughes et al, 2007;Calvete et al, 2012) and clinical trials Leathwick et al, 2008;Waghorn et al, 2008Waghorn et al, , 2009 have been performed to investigate the association between putative risk factors and AHR. While all these studies may provide valuable information in isolation, they sometimes describe conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research highlights that this practice may increase the selection pressure for resistance (e.g. Hughes et al 2007). Therefore, this result should be taken with caution.…”
Section: Initial Larvae Pasture Densitymentioning
confidence: 84%
“…Moreover, nutrient supplementation is expensive in Western Australia, particularly in extensive farming systems. In contrast, refugia is easy to implement on-farm and appears a practical means of slowing the development of resistance (Van Wyk et al 2006;Hughes et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation